Mapping mangrove sustainability in the face of sea level rise and land use: A case study on Leizhou Peninsula, China. (1st January 2023) - Liang, Shanshan; Hu, Wenjia; Liu, Jie; Su, Shangke; Chen, Guangcheng; Chen, Shunyang; Xie, Bin; Du, Jianguo; Liu, Wenhua; Chen, Bin
Abstract: Habitat loss and degradation of mangrove forests can be caused by both sea level rise (SLR) and unsustainable land practices. Current long-term change projections are often based on changes to mangrove extent; however, this may overlook fragmentation and the associated habitat resilience decline and therefore fail to adequately reveal the risks to mangrove habitats. A mangrove sustainability index (MSI) was proposed in this study to assess the impact of SLR and land use on mangrove habitats. The index consists of four components: habitat area change, habitat quality, landscape pattern, and protection ratio. Ecological models and landscape models were combined to calculate the MSI. Considering the SLR under RCP4.5 and RCP8.5 and land use strategies, four scenarios were set with prediction periods of base year (2020) to 2050 and 2100. The Leizhou Peninsula, China was used as the case study. The results showed that dual stressors would reduce the extent of mangroves by 16.6%–56.2%. Habitat quality was sensitive to land use change but was not affected by SLR. Landscape pattern and protection ratio were influenced by SLR but less effected by land use. In all scenarios, mangroves tended to migrate out of the protected areas, with protection ratio decreasing from 37% to 16.9%–29.9%. Newly expanding habitats may suffer from patch fragmentation and low connectivity. Unsustainable mangrove distribution sites on Leizhou Peninsula were identified as hotspots for management. Projections under different scenarios showed that some unsustainable sites could be reversed to sustainable sites through improvements in land use policies. The proposed approach could provide essential tools for the formulation of mangrove conservation and restoration strategies adapted to climate change. Graphical abstract: Image 1 Highlights: A novel mangrove sustainability index consisting of four components was proposed. Mangrove habitat loss rates would range from 16.6% to 56.2% under dual stressors of SLR and land use. Newly expanding habitats may suffer from patch fragmentation and low connectivity. Some unsustainable sites could be reversed to sustainable ones under appropriate land use policies.